2022
DOI: 10.1111/pai.13844
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Makrinioti H et al.

Abstract: To the Editor, We read with great interest the article titled "The role of respiratory syncytial virus-and rhinovirus-induced bronchiolitis in recurrent wheeze and asthma-A systematic review and meta-analysis" published in the recent issue of the Pediatr Allergy Immunol. This article is the first to compare between-virus differences in the magnitude of virus-recurrent wheeze and virus-childhood asthma outcomes. The authors concluded that rhinovirus-induced bronchiolitis was more closely associated with the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 4 publications
1
28
0
1
Order By: Relevance
“…The remaining 89 full-text articles were evaluated for eligibility, 62 of which were removed because they provided outdated preliminary results or lacked valid data. Thus, 27 prospective studies were included in the final qualitative and quantitative synthesis (Figure 1). The geographic distribution of included studies is shown in eFigure 1 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 89 full-text articles were evaluated for eligibility, 62 of which were removed because they provided outdated preliminary results or lacked valid data. Thus, 27 prospective studies were included in the final qualitative and quantitative synthesis (Figure 1). The geographic distribution of included studies is shown in eFigure 1 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the 27 trials included 815 patients with esophageal cancer being treated with neoadjuvant immunotherapy combined with chemotherapy who were available for analysis. All studies were open-label, phase 2 non-RCTs, and 25 of them were single-group and 2 were dual-group trials . Twenty-three trials enrolled patients with ESCC and applied anti–PD-1 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-formulating two mRNAs in one LNP, instead of co-administering two LNP single-loaded with one mRNA, would in principle be possible, but this likely doesn't add much value in vaccination setups. When it comes to simultaneously producing proteins at the single-cell level, however, it has been shown that 'together is better', especially when aiming to ratiometrically control protein expression 2 . Co-formulating two RNAs in one LNP is furthermore crucial for efficient CRISPR-based gene editing.…”
mentioning
confidence: 99%